Elemental and isotopic compositions of New Zealand regional soils identifies human and climate-induced effects. (August 2022) - Rogers, Karyne M.; Martin, Adam P.; Pradel, Giovanni; Yuan, Yuwei; Zhang, Yongzhi; Turnbull, Rose E.
Abstract: A regional soil study of 61 sites from the Wairau and Awatere Valleys, Marlborough region, New Zealand characterised the geochemical baselines of different land-use types. The study used three stable isotopes ( δ 13 C, δ 15 N, δ 34 S) and 65 elements to describe the influence of parent-rock geology, human and climate-induced effects and natural transport processes on the soil quality and soil health of this region. The temperate Marlborough region produces high quality wine and the elemental and isotopic composition of a subset of vineyard soils are examined in more detail to identify soil characteristics specific to this agriculturally productive region. Higher levels of Cd, K, N, P, S and Zn were found in vineyard soils compared to forested and rural soils, indicative of anthropogenic agricultural inputs. Stable isotopes in vineyard soils had higher δ 13 C and δ 15 N values and lower δ 34 S values than forested and rural soils, typical of more highly cultivated soils. The natural geogenic inputs from the ultra-mafic mountains enclosing the Wairau and Awatere Valleys were geochemically distinct from localised anthropogenic contaminants. Comparisons with a further 240 New Zealand urban (Dunedin) and rural (Southland-Otago region) soils suggests the elemental contaminants found in the Marlborough vineyard soils may be specific to high-yielding agricultural zones across New Zealand. Highlights: Soils from Marlborough region were characterised by their land-use type. Stable isotopes (C, N, S) and elemental contents discriminated land-use activities. Higher levels of Cd, K, N, P, S and Zn were found in cultivated vineyard soils. Higher δ 13 C and δ 15 N values and lower δ 34 S values were found in vineyard soils. No significant heavy metal build-up was found in vineyard soils.